THE INFLUENCE OF COORDINATION COMPOUNDS OF GERMANIUM (IV) WITH NITROBENZOIC AND CHLORBENZOICACIDS SALICYLALHYDRAZONES ON THE CONTENT OF THE BASIC LYMPHOCYTES POPULATIONS AND SUBPOPULATIONS IN THE COURSE OF INFLAMMATION IN MICE - О. В. Нікітін; Б. М. Галкін; Т. О. Філіпова; I. Й. Сейфулліна; Н. В. Шматкова (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2009)
It was shown that in zymozan induced inflammation CD4/CD8 ratio increased for 1.8 times, that showed immune system activation. Also on the background of inflammation NK-cells content increased for 70%. Studied coordination compounds of germanium decrease the level of NK-cells and T-helpers but increase the level of T-suppressors that result in decreasing of CD4/CD8 ratio.